Epitranscriptomic profiling of m5C RNA methylation reveals a dynamic response to TSWV infection in tomato - Zhao, Xinyi; Gong, Yanwei; Jiao, Yubing; Zhang, Wanhong; An, Dong; Wang, Yingwen; Lv, Binna; Li, Ying; Shen, Lili; Yang, Jinguang (Frontiers in Plant Science, 2026)
Cytosine-5 methylation (m5C) is a crucial epitranscriptomic mark in eukaryotes that modulates RNA stability and gene expression. While the roles of m5C are partially understood in model plants, its function in horticultural crops under biotic stress remains largely unexplored. To address this gap, we investigated the role of m5C modification in tomato response to tomato spotted wilt virus (TSWV) infection. We constructed the first comprehensive m5C epitranscriptomic map in Solanum lycopersicum. To investigate its role in plant immunity, we further profiled the dynamic changes of the m5C methylome upon TSWV infection, followed by integrative multi-omics analysis. Functional validation was performed through virus-induced gene silencing (VIGS) of the key RNA methyltransferase gene SlTRM4B. The m5C epitranscriptomic map revealed conserved modification patterns with enrichment at transcription start and stop sites. Upon TSWV infection, a global increase in m5C modification levels was observed across the transcriptome, which was correlated with the significant upregulation of RNA methyltransferase (RCMT) family genes, particularly SlTRM4B. Integrative multi-omics analysis revealed that genes exhibiting both hypermethylation and increased expression were significantly enriched in the plant-pathogen interaction pathway. VIGS of SlTRM4B demonstrated that this methyltransferase is essential for maintaining the stability of its target transcripts under TSWV infection, leading to enhanced disease susceptibility. Collectively, our findings demonstrate that SlTRM4B-mediated m5C RNA methylation fine-tunes post-transcriptional regulation to reprogram the transcriptome for disease resistance in tomato. This work provides novel insights into the epitranscriptomic mechanisms governing plant responses to viral pathogens.